2008
DOI: 10.1186/1471-2296-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Determining patient and primary care delay in the diagnosis of cancer – lessons from a pilot study of patients referred for suspected cancer

Abstract: Background: There is no validated way of measuring diagnostic delay in cancer, especially covering patient and primary care delays. An instrument is needed in order to determine the effect of potential interventions to reduce delay and improve cancer morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 8 publications
(8 reference statements)
0
24
0
Order By: Relevance
“…A previous report suggests that the collection of data from medical records is more accurate than the patient interview alone [18]. …”
Section: Methodsmentioning
confidence: 99%
“…A previous report suggests that the collection of data from medical records is more accurate than the patient interview alone [18]. …”
Section: Methodsmentioning
confidence: 99%
“…These factors are also associated with the way individuals access hospital care for cancer 26. Methodological differences might be blamed for inconsistencies in findings between studies of patient delay 27. However, overcoming such differences will not in itself provide explanations for correlations between ‘factors’ such as socioeconomic circumstance and delay, or provide deeper understanding of the social processes through which these relationships are produced.…”
Section: Delaymentioning
confidence: 99%
“…Several instruments to estimate the likelihood of delay in seeking medical attention if a cancer symptom were to present have been validated in asymptomatic patients [18,19], but no studies have assessed delay among breast cancer patients. Some breast cancer delay studies refer to questionnaires based on previous study results or describe the results of pilot studies, but no validity and reliability measures are specified [20-22]. We found only one study in which the reliability and validity of self-reported symptoms and dates of diagnostic tests was measured, but this study surveyed patients with colon cancer [23], which is characterised by a completely different set of symptoms, natural history and illness behaviour compared to breast cancer [24-27].…”
Section: Introductionmentioning
confidence: 99%